Nitrogen loading enhances phosphorus limitation in terrestrial ecosystems with implications for soil carbon cycling. (19th September 2022) - Luo, Min; Moorhead, Daryl L.; Ochoa‐Hueso, Raúl; Mueller, Carsten W.; Ying, Samantha C.; Chen, Ji
Abstract: Increased human‐derived nitrogen (N) loading in terrestrial ecosystems has caused widespread ecosystem‐level phosphorus (P) limitation. In response, plants and soil micro‐organisms adopt a series of P‐acquisition strategies to offset N loading‐induced P limitation. Many of these strategies impose costs on carbon (C) allocation by plants and soil micro‐organisms; however, it remains unclear how P‐acquisition strategies affect soil C cycling. Herein, we review the literature on the effects of N loading on P limitation and outline a conceptual overview of how plant and microbial P‐acquisition strategies may affect soil organic carbon (SOC) stabilization and decomposition in terrestrial ecosystems. Excessive input of N significantly enhances plant biomass production, soil acidification, and produces plant litterfall with high N/P ratios, which can aggravate ecosystem‐level P limitation. Long‐term N loading can cause plants and soil micro‐organisms to alter their functional traits to increase P acquisition. Plants can release carboxylate exudates and phosphatases, modify root morphological traits, facilitate the formation of symbiotic associations with mycorrhizal fungi and stimulate the abundance of P‐mineralizing and P‐solubilizing micro‐organisms. Releasing carboxylate exudates and phosphatases could accelerate SOC decomposition, whereas changing symbiotic associations and root morphological traits (e.g. an increase in fine root length) may contribute to higher SOC stabilization. Increased relative abundances of P‐mineralizing and P‐solubilizing bacteria can accelerate P mining and SOC decay, which may decrease microbial C use efficiency and subsequently lower SOC sequestration. The trade‐offs between different plant P‐acquisition strategies under N loading should be among future research priorities due to their cascading impacts on soil C storage. Quantifying ecosystem thresholds for P adaption to increased N loading is important because P‐acquisition strategies are effective when N loading is below the N threshold. Moreover, understanding the response of P‐acquisition strategies at different levels of native soil N availability could provide insight to divergent P‐acquisition strategies across sites and ecosystems. Altogether, P‐acquisition strategies should be explicitly considered in Earth System Models to generate more realistic predictions of the effects of N loading on soil C cycling. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.